The end of an era: Asian NIEs in the global economy - Clark, G (Blackwell Publishing, 1994)
Hong Kong, Singapore, Korea, and Taiwan (the Asian newly industrialized economies [NIEs]) were the economic success stories of the 1970s and 1980s. While there are a number of competing explanations for their rapid growth, some focusing upon the process of export-led development, the Asian NIEs face a more hostile global competitive environment than heretofore acknowledged. Their competitiveness in labor-intensive and traded-goods manufactured industries has been undermined by new competitors including the ASEAN countries of Indonesia, Malaysia, Thailand, and the Philippines, as well as China. With new competitors, the rise of trading blocs, and the shrinkage of export surpluses (over imports) it is doubtful if the NIEs will be able to sustain past rates of growth over the coming years. The capacity to adjust efficiently to changing circumstances has become a vital determinate of long-term growth of the NIEs. Whatever the virtues of past state-based industrial policies, restructuring is now a very important part of the life of firms in the NIEs’labor-intensive industries. Moreover, the significance of these industries in each of the NIEs has been undercut by the growing importance of the global finance industry and its attendant political economy.